Computed Tomography Perfusion Data for Acute Ischemic Stroke Evaluation Using Rapid Software: Pitfalls of Automated Postprocessing. Issue 1 (January 2020) - Kauw, Frans; Heit, Jeremy J.; Martin, Blake W.; van Ommen, Fasco; Kappelle, L. Jaap; Velthuis, Birgitta K.; de Jong, Hugo W.A.M.; Dankbaar, Jan W.; Wintermark, Max
Abstract : Abstract: Computed tomography perfusion (CTP) is increasingly used to determine treatment eligibility for acute ischemic stroke patients. Automated postprocessing of raw CTP data is routinely used, but it can fail. In reviewing 176 consecutive acute ischemic stroke patients, failures occurred in 20 patients (11%) during automated postprocessing by the RAPID software. Failures were caused by motion (n = 11, 73%), streak artifacts (n = 2, 13%), and poor contrast bolus arrival (n = 2, 13%). Stroke physicians should review CTP results with care before they are being integrated in their decision-making process. Abstract : Supplemental digital content is available in the text.